Eleven new species of the genus Cluzobra Edwards (Diptera, Mycetophilidae, Sciophilinae) from the Atlantic Forest of Brazil - de Souza Amorim, Dalton; Oliveira, Sarah Siqueira (Zootaxa, 2008)
Eleven new species of the sciophiline genus Cluzobra Edwards are described and illustrated – Cluzobra triocellata, sp.n., Cluzobra accola, sp.n., Cluzobra claripennis, sp.n., Cluzobra papaveroi, sp.n., Cluzobra coptolithus, sp.n., Cluzobra vockerothi, sp.n., Cluzobra sapiranga, sp.n., Cluzobra fluminense, sp.n., Cluzobra fritzmuelleri, sp.n., Cluzobra spinata, sp.n., Cluzobra elpidia, sp.n. Additional specimens of C. fuscipennis Edwards, C. plaumanni Edwards, and C. binocellaris (Edwards) have been identified, extending the distribution range of these species. The species were identified and described based on 173 specimens at different latitudes along the Atlantic Forest in eastern Brazil and northern Argentina. The position of the new species in the groups of species proposed for the genus in the literature is considered. Three areas of endemism are identified for the group, one from southern Brazil, northern Argentina and Paraguay northwards to areas at higher altitudes in the States of Minas Gerais and Rio de Janeiro, one from southern Bahia to the extreme north of the Atlantic Forest, in the State of Rio Grande do Norte, and one in west State of São Paulo, extending west and northwards into the states of Mato Grosso do Sul and Goiás. This paper raises the number of known Cluzobra to 41 species.